Malaria: An Unseen Enemy Threatening to Mankind - Pawar, Sandip; Shende, Pravin (Journal of Tropical Diseases and Medicine, 2018)
The research work on malarial infection and malarial treatment has been increased tremendously over the years due to increased resistance of parasites to antimalarial drugs. To overcome the developed resistance, antimalarial drugs are used in combination. But eventually the amount of drugs administered increase with the resistance and extend to adverse effects. Many innovative, sophisticated delivery systems have been developed to increase the adequacy, competency and efficiency of antimalarial drugs. But it is predicted that these new inventions will also acquire resistance with time. Globally, it is seen that the countries which have low standards of hygiene have high levels of malarial infection. There are various antimalarial techniques developed and are slowly being adopted worldwide. But the first step is to maintain the hygiene and cleanliness so that mosquitoes will not harvest.
Keywords: Malarial infection; Resistance; Combination therapy; Preventive methods